A NEW SPECIES OF HEDYOTIS (RUBIACEAE) FROM INDIA - Karuppusamy, S.; Ravichandran, V. (Edinburgh Journal of Botany, 2014)
A new species, Hedyotis rajasekaranii Karupp. & Ravichandran (Rubiaceae), is described from the Megamalai Hills of the Western Ghats in Tamil Nadu, southern India.
Keywords: Conservation status; Hedyotis; India; Rubiaceae